Approaches to Measure the Health-related Quality of Life among Patients with Cardiac Problems: A Narrative Review - Karmacharya, Ranjita; Paul, T David Ratna; Sharma, Muna (Journal of Nursing and Health Sciences Nepal, 2025)
Introduction: The health-related quality of life (HRQoL) of cardiac patients provides a picture of the patient’s perspectives on their psychological, social, and physical well-being. Assessment of HRQoL helps to understand how disease conditions and treatment modalities influence overall health outcomes. Various validated instruments are available to measure HRQoL of patients with cardiac problems. Thus, this review aimed to discuss the commonly used generic and disease-specific tools for measuring HRQoL in cardiac patients. Methods: For the study, EMBASE, Medline, and CINHAL databases were searched which was published between 2018 and 2025. Titles and abstracts were screened for eligibility criteria, followed by full-text review of potentially relevant studies. Results: Seven studies were included in the analysis. Generic questionnaires primarily assess subjective well-being in relation to overall health. Specific instruments reflected the specific disease›s impacts on a person’s life. For the measurement of general health WHOQOL-100, WHOQOL-BREF were developed by the World Health Organization, and the EuroQol Group developed EuroQol 5 instrument. These tools are widely used in the field of cardiac disease. The Seattle Angina Questionnaire is used to assess the effect of angina on cardiac patients’ everyday life, while the Kansas City Cardiomyopathy Questionnaire and Minnesota Living tool measures disease-specific symptoms, especially for Heart Failure. Conclusions: Assessment of quality of life is essential in the medical field, as it provides holistic information on the health and general well-being of the patients. So, healthcare professionals can deliver patient-centered care by identifying the hidden needs of the patients.